Beach season - Jackson, Lisa; Chamberlin, Holly, 1962-; Lamb, Cathy; Noonan, Rosalind (Kensington Books, 2012)
"Golden sand, pounding surf, a sense of endless possibility-and four unforgettable stories of love, friendship, and second chances ..."--P. [4] of cover.